Modeling current and future distributions of invasive Asteraceae species in Northeast China - Jie Yu; Lan Li; Hangnan Yu; Weihong Zhu; Meizhu Hou; Jiangtao Yu; Meng Yuan; Zhanqiang Yu (Scientific Reports)
Abstract The ecological balance and agricultural productivity of northeastern China are seriously threatened by the long-term invasion and spread of Asteraceae plants, which have severely disrupted the region’s biodiversity and ecosystem stability. Ambrosia artemisiifolia L., Ambrosia trifida L., and Erigeron canadensis L. are Class 1 malignant invasive species widely distributed across northeastern China. In this context, we selected 36 predictor variables and utilized the MaxEnt model to investigate the influence of current climate on their distribution patterns. Using future climate data, we projected shifts in the distribution dynamics of these three Asteraceae species for two time periods (2041–2060 and 2061–2080) under three climate change scenarios (SSP126, SSP245, and SSP585). The MaxEnt model demonstrated a good predictive impact, with an average area under the curve (AUC) of 0.918. Currently, the three Asteraceae species are primarily found in the southern part of northeastern China. However, due to future climatic changes, their distribution centroids are gradually shifting southwest, leading to an increase in the area of highly suitable zones for these species. Moreover, trend analysis revealed that the potential distribution changes of highly suitable zones for the three Asteraceae species in the southwestern northeastern China are likely to experience an increasing invasive trend under various future climate models. This study provides initial insights into the distribution dynamics of Asteraceae species in northeastern China under climate change, enabling the formulation of plans for managing and preventing the risks and impacts of invasive species.